(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
The perfect aspect is a retrospective aspect that encodes the current relevance of a previous event. In this work, we propose a semantic and grammatical category labeled as antiperfect that, in contrast to the perfect aspect, encodes the non-validity of a previous eventuality in speech time. Given that, as the perfect aspect, the antiperfect is subject to the current relevance of a previous situation, we propose that this is a second type of retrospective aspect. After reviewing the descriptions of perfect by Comrie (1976), Dik (1997) and Nishiyama & Koenig (2010), and the description of discontinuous past by Plungian & van der Auwera (2006), we analyze how the antiperfect is grammatically encoded in Mapudungun by means of the morpheme –fu. We focus the analysis of this category on its semantic-pragmatic description, its relation to aktionsart, and the role of context in its interpretation